К вопросу об этнической принадлежности крымчаков - Ачкинази, И.В. (Материалы по археологии, истории и этнографии Таврии, 1996)
На территории бывшего СССР имеются, по крайней мере, три этнических общности, не включая русских геров (8), представители которых обладают устойчивым нееврейским этническим самосознанием и при этом исповедовали в прошлом и исповедуют в настоящем иудаизм или караимизм. Однако, при рассмотрении проблем истории этих общностей большинством исследователей не принимается во внимание исторически обусловленный фактор их самоидентификации, постулируется тезис о национальном характере иудаизма. Вопросам конфессионального сознания и этнического самосознания крымчаков посвящена настоящая статья. There is a problem to define the ethnic affiliation of the Krymchaks. Many scholars who studied different aspects of the Krymchaks’ history and culture proceeded on confession factor, ignoring some medieval, modern and contemporary sources, testifying the Krymchaks consciousness, characteristic for the representatives of this Crimean commonality. Those scholars believed that Turk language, Turk elements in clothes, ways of life and traditions were the result of Tatars’ influence. Studying the aggregate of confession and ethnic components enables us to draw to a conclusion that the Krymchaks are an ethnoconfessial commonality, which was formed in the Medieval period of the history of the Crimea on the basis of reformed Jewish rite at the beginning of the 16th century from the representatives of different ethnic groups - long-time resident Turk Jewish community that survived from the Khazar period of Crimean history and integrated some families of Kievan and Genoese Jews.